Polarizing device with high extinction ratio and double-layer grating structure

By combining the SiO2 dielectric grating layer and metal layer wire grid structure on a quartz substrate, adjusting the grating structure parameters, a double-layer grating structure polarization device with high extinction ratio is achieved, solving the problem of low extinction ratio in the near-infrared band and improving polarization selection and manufacturing feasibility.

CN119270411APending Publication Date: 2025-01-07BEIJING INFORMATION SCI & TECH UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411562069.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing metal array polarization devices have low extinction ratios in the near-infrared band and are difficult to prepare, making it difficult to meet the polarization information detection needs in complex and harsh environments.

Method used

A high extinction ratio double-layer grating structure polarization device is designed, including a quartz substrate, SiO2 dielectric grating layer and metal layer wire grid structure. By adjusting the unit structure, thickness and grating width of the double-layer grating structure, it can realize the near-infrared band. Extinction ratio of more than 75dB within 1 to 2 μm.

Benefits of technology

It significantly improves polarization selectivity and detection sensitivity, and is suitable for infrared detectors, polarization optical sensors and imaging systems, simplifies manufacturing processes and improves yield.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119270411A_ABST
    Figure CN119270411A_ABST
Patent Text Reader

Abstract

The invention relates to the field of optical devices, and discloses a high-extinction-ratio polarization device with a double-layer grating structure, which comprises a quartz substrate, a SiO2 medium grating layer and a metal layer wire grating structure, and is characterized in that the SiO2 medium grating layer is arranged on the quartz substrate; the metal layer wire grating structure is arranged on the SiO2 medium grating layer, and the metal layer wire grating structure and the SiO2 medium grating layer jointly form a double-layer grating structure; by adjusting the unit structure, the thickness and the grating width of the double-layer grating structure, the high-extinction-ratio polarization device with the double-layer grating structure has the extinction ratio of more than 75dB within the near-infrared band of 1-2 microns. The polarization device has an extinction ratio of more than 75dB in a near-infrared band (1-2 mu m), which is obviously higher than that of a traditional polarization device with a single-layer grating structure, and the high extinction ratio means that the polarization device can more effectively block polarized light in a specific direction and only allows transmission of polarized light in another direction, so that the polarization device has a wide application prospect. And the polarization selectivity and the detection sensitivity are greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of optical devices, in particular to a high extinction ratio double-layer grating structure polarization device. Background Art

[0002] As one of the basic properties of light, polarization is widely used in the fields of communication, imaging, optical encryption, etc. Its generation, regulation and detection are different from the traditional optical imaging technology that relies on light intensity information to achieve target detection and recognition. Polarization detection technology is more likely to suppress background interference, highlight target features, and has strong penetration ability, thereby significantly improving the accuracy of detection. However, in the near-infrared band, the existing metal array polarization devices still have the problem of low extinction and difficult preparation.

[0003] Considering the requirements for device quality and volume in terms of device mounting, reducing the volume of polarization devices is the main research direction under the premise of meeting the light field quality. Due to its unique light field modulation mechanism, metasurface materials have the advantages of being light, thin, simple, and having a wide range of applicable wavelengths, and have become one of the solutions for miniaturization and lightweight polarizers. Reducing the size of polarization devices, integrating them with imaging sensors, miniaturizing and integrating polarization detection systems, and improving polarization detection performance require weighing various optical performance index parameters to meet market application needs. However, most of the grating polarization devices currently designed are performed in the visible light band region, and in complex and harsh environments, in order to improve the accuracy and stability of polarization information detection, it is necessary to select polarization information in the near-infrared band. Therefore, there are still many challenges in the development of near-infrared micro-nano polarization devices based on metasurfaces, which has become an urgent problem that researchers at home and abroad need to solve. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention provides a high extinction ratio double-layer grating structure polarization device to solve the problem that the currently designed grating polarization devices mostly perform in the visible light band region, while in complex and harsh environments, it is necessary to select polarization information in the near-infrared band.

[0005] To achieve the above objectives, the present invention is implemented through the following technical solutions: a high extinction ratio double-layer grating structure polarization device, including a quartz substrate, a SiO2 dielectric grating layer and a metal layer wire grid structure,

[0006] The SiO2 dielectric grating layer is arranged on a quartz substrate;

[0007] The metal layer wire grid structure is arranged on the SiO2 dielectric grating layer, and the metal layer wire grid structure and the SiO2 dielectric grating layer together form a double-layer grating structure;

[0008] By adjusting the unit structure, thickness and grating width of the double-layer grating structure, the high extinction ratio double-layer grating structure polarization device has an extinction ratio of more than 75dB in the near-infrared band of 1 to 2μm.

[0009] Preferably, the thickness of the SiO2 dielectric grating layer is 200-300 nm, and the thickness of the metal gold grating layer is 150-250 nm.

[0010] Preferably, the period P of the unit structure of the double-layer grating is 150-250nm, the width W of the metal gold grating layer is 100-150nm, the width w of the SiO2 dielectric grating layer is 70-90nm, and the width of the metal gold grating layer is the same as the width w of the SiO2 dielectric grating layer, which is 70-90nm. The width W of the bottom metal gold is 100-150nm, and it covers the entire period with the SiO2 dielectric grating layer, and the duty cycle f is 0.3-0.5.

[0011] Preferably, a method for preparing a high extinction ratio double-layer grating structure polarization device comprises the following steps:

[0012] S1. Cleaning the quartz substrate;

[0013] S2, depositing a SiO2 layer on a quartz substrate;

[0014] S3. Spin-coat photoresist on the SiO2 layer, perform exposure and etching, and form a metal layer wire grid structure by metal evaporation technology.

[0015] Preferably, in step S1, cleaning the quartz substrate comprises ultrasonic cleaning using acetone, isopropanol and deionized water for 5 to 15 minutes each.

[0016] Preferably, in the step S2, a non-doped SiO2 layer with a thickness of 200 to 300 nm is deposited on the substrate using plasma enhanced chemical vapor deposition.

[0017] Preferably, in the step S3, the thickness of the photoresist after spin coating is 250-300 nm, the pre-baking temperature is 150-200° C., and the time is 1-3 minutes.

[0018] Preferably, in the step S3, the SiO2 layer is etched using inductively coupled plasma reactive ion etching with an etching depth of 200 to 300 nm to form a grating structure.

[0019] Preferably, in step S3, the metal layer wire grid structure is gold, and a gold layer with a thickness of 150 to 250 nm is deposited using metal evaporation technology.

[0020] The present invention provides a high extinction ratio double-layer grating structure polarization device, which has the following beneficial effects:

[0021] 1. The polarization device of the present invention has an extinction ratio of more than 75 dB in the near-infrared band (1-2 μm), which is significantly higher than that of the traditional single-layer grating structure polarization device. The high extinction ratio means that the polarization device can more effectively block polarized light in a specific direction, while only allowing polarized light in another direction to be transmitted, greatly improving the polarization selectivity and detection sensitivity.

[0022] 2. The device of the present invention exhibits stable polarization characteristics in the near-infrared band (1-2 μm), which makes it suitable for a variety of near-infrared applications, such as infrared detectors, polarization optical sensors, and imaging systems. In many practical application scenarios, such as biomedical imaging, remote sensing technology, and environmental monitoring, the polarization information of the near-infrared light band has significant advantages for target recognition and background suppression.

[0023] 3. The combination of SiO2 dielectric grating and metal grating in the double-layer grating structure of the present invention significantly improves the overall performance of the device. At the same time, the etching step of the single-layer metal grating is avoided during the preparation process, which simplifies the manufacturing process and reduces the high requirements for equipment and process accuracy. In particular, the deposition of the metal grating layer directly avoids the technical difficulties of nanoscale metal etching, significantly improving the manufacturing feasibility and yield rate of the device. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The three-dimensional structure and cross-sectional schematic diagram of the double-layer grating of the present invention;

[0025] Figure 2 It is a schematic diagram of the transmittance and extinction ratio comparison curve of the double-layer grating structure designed for the present invention under x-polarized light incidence and a single-layer grating;

[0026] Figure 3 It is a schematic diagram of the sample preparation process of the present invention;

[0027] Figure 4 Schematic diagram of the test optical path of the present invention. DETAILED DESCRIPTION

[0028] The technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings of the present invention.

[0029] Please see attached Figure 1 -Attached Figure 4 The embodiment of the present invention provides a high extinction ratio double-layer grating structure polarization device, comprising a quartz substrate, a SiO2 dielectric grating layer and a metal layer wire grid structure,

[0030] The SiO2 dielectric grating layer is disposed on a quartz substrate;

[0031] The metal layer wire grid structure is arranged on the SiO2 dielectric grating layer, and the metal layer wire grid structure and the SiO2 dielectric grating layer together form a double-layer grating structure;

[0032] By adjusting the unit structure, thickness and grating width of the double-layer grating structure, the high extinction ratio double-layer grating structure polarization device has an extinction ratio of more than 75dB in the near-infrared band of 1 to 2μm.

[0033] Specifically, the polarization device is a polarization device with a high extinction ratio (greater than 75 dB) in the near-infrared band. It consists of three main parts: a quartz substrate, a SiO2 dielectric grating layer and a metal layer (Au) wire grid structure.

[0034] Quartz substrate: Quartz is a highly light-transmitting material with good optical properties and is widely used in optical devices. Quartz is used as the substrate material in the present invention because it has low light absorption in the near-infrared band of 1 to 2 μm and can provide good transmission performance.

[0035] SiO2 dielectric grating layer: SiO2 is silicon dioxide, which has good light transmittance and stability. The dielectric grating layer is formed on a quartz substrate by etching or deposition process, which can affect the phase and transmission direction of the incident light.

[0036] Metal layer (Au) wire grid structure: The metal layer is gold (Au) material to form a wire grid structure. Gold has good chemical stability and conductivity, and is used as a reflective and absorbing layer in optical devices to enhance the response to specific polarized light.

[0037] Double-layer grating structure: The present invention adopts a double-layer structure design, that is, a combination of a SiO2 dielectric grating layer and a metal wire grating layer. This design can provide a higher extinction ratio, thereby improving the selectivity and performance of polarized light.

[0038] By adjusting the unit structure, thickness and width of the grating, efficient control of polarized light in the near-infrared band (1-2 μm) can be achieved, thereby achieving a high extinction ratio.

[0039] The thickness of the SiO2 dielectric grating layer is 200-300 nm, and the thickness of the metal gold grating layer is 150-250 nm.

[0040] Specifically, the thickness range of the SiO2 dielectric grating layer and the metal layer is:

[0041] SiO2 dielectric grating layer: Its thickness is 200-300nm. The choice of thickness has an important influence on the light transmittance, control ability and process realization of the device.

[0042] Metal layer (Au): Its thickness is 150-250nm. The thickness of the metal layer will affect the absorption characteristics, reflectivity and extinction ratio of the polarizer.

[0043] The choice of thickness is crucial to the optical performance of the device, because grating structures of different thicknesses will modulate the incident light differently, thus affecting the overall polarization performance of the device.

[0044] The period P of the unit structure of the double-layer grating is 150-250nm, the width W of the metal gold grating layer is 100-150nm, the width w of the SiO2 medium grating layer is 70-90nm, and the duty cycle f is 0.3-0.5.

[0045] Specifically, the grating period (P) is 150-250 nm, which refers to the repetition spacing of the grating unit structure. The size of the grating period will directly affect the optical response frequency of the device and its working effect in different wavelength ranges.

[0046] The width of the metal grating layer (W): 100-150nm, which refers to the lateral size of the metal grid. The adjustment of the width can change the transmission or reflection effect of different polarized light.

[0047] The width of the dielectric grating layer (w): is 70~90nm, which refers to the lateral size of the SiO2 dielectric grating.

[0048] Duty cycle (f): Duty cycle is defined as the ratio of grating line width w to period P, i.e. f = w / P, and the duty cycle is between 0.3 and 0.5. The size of the duty cycle will affect the modulation effect of the grating on the incident light, including reflectivity and transmittance.

[0049] A method for preparing a high extinction ratio double-layer grating structure polarization device comprises the following steps:

[0050] S1. Cleaning the quartz substrate;

[0051] S2, depositing a SiO2 layer on a quartz substrate;

[0052] S3. Spin-coat photoresist on the SiO2 layer, perform exposure and etching, and form a metal layer wire grid structure by metal evaporation technology.

[0053] Specifically, quartz substrate cleaning: first, use acetone, isopropyl alcohol and deionized water to ultrasonically clean the quartz substrate for 5 to 15 minutes each to remove impurities and pollutants on the surface to ensure the adhesion and quality between the deposited layer and the substrate in the subsequent process.

[0054] SiO2 layer deposition: A layer of SiO2 is deposited on a quartz substrate using plasma enhanced chemical vapor deposition (PECVD) with a thickness between 200 and 300 nm. PECVD is a chemical vapor deposition technique that uses high energy plasma to accelerate the chemical reaction of reactants to form a dense and uniform film.

[0055] Photoresist spin coating and exposure: Spin-coat the photoresist on the deposited SiO2 layer with a thickness of 250-300nm. After the photoresist is spin-coated, it needs to be pre-baked at a temperature of 150-200℃ for 1-3 minutes. Then the photoresist is exposed to electron beams to form the grating pattern. The developed photoresist part will be used as a mask for the etching process.

[0056] SiO2 etching: Use inductively coupled plasma reactive ion etching (ICP-RIE) to etch the SiO2 layer to a depth of 200 to 300 nm to form the required grating structure. ICP-RIE is a dry etching technology that etches materials through plasma, with the advantages of high anisotropy and precise control.

[0057] Metal evaporation technology forms a metal layer: a metal layer (Au) is deposited on the etched SiO2 grating with a thickness of 150 to 250 nm. Metal evaporation is a physical vapor deposition method that heats the metal material to evaporate it, and then condenses on the sample surface to form a uniform film.

[0058] In step S1, the quartz substrate cleaning includes ultrasonic cleaning using acetone, isopropyl alcohol and deionized water for 5 to 15 minutes respectively.

[0059] Specifically, the cleaning of the quartz substrate is an important step that cannot be ignored in the entire preparation process. It includes:

[0060] Acetone cleaning: Acetone is an organic solvent that can effectively remove oil and organic matter.

[0061] Isopropyl alcohol cleaning: Isopropyl alcohol can further remove acetone residues and other impurities while increasing the hydrophilicity of the surface.

[0062] Deionized water cleaning: Deionized water can remove inorganic salts and other impurities, ensuring that there is no residual material on the surface.

[0063] Ultrasonic cleaning: Perform ultrasonic cleaning for 5 to 15 minutes in each cleaning agent to completely remove impurities attached to the surface through ultrasonic vibration.

[0064] In step S2, a non-doped SiO2 layer with a thickness of 200 to 300 nm is deposited on the substrate using plasma enhanced chemical vapor deposition.

[0065] In step S3, the thickness of the photoresist after spin coating is 250-300 nm, the pre-baking temperature is 150-200° C., and the time is 1-3 minutes.

[0066] In step S3, the SiO2 layer is etched by inductively coupled plasma reactive ion etching to a depth of 200 to 300 nm to form a grating structure.

[0067] Specifically, a SiO2 layer is deposited on a quartz substrate using plasma enhanced chemical vapor deposition (PECVD) technology. PECVD can deposit high-quality SiO2 thin films at low temperatures, and the film thickness can be controlled between 200 and 300 nm. SiO2 has good optical transparency, especially in the near-infrared band, and is suitable as part of the grating structure.

[0068] Photoresist processing and etching process

[0069] Photoresist spin coating and pre-baking: Photoresist is a photosensitive material used for patterning surfaces. Spin 250-300nm of photoresist on the SiO2 layer to form a precise pattern. After spin coating, pre-baking is performed at a temperature of 150-200℃ for 1-3 minutes to remove the solvent and enhance the adhesion of the photoresist.

[0070] Electron beam exposure and development: After exposure, the developer is used to dissolve and remove the unnecessary photoresist parts, retaining the required mask structure.

[0071] ICP-RIE etching: The SiO2 layer is etched by inductively coupled plasma reactive ion etching technology to form a grating structure. The etching depth is controlled at 200-300nm. The high anisotropy of ICP-RIE makes the etching have a high verticality, ensuring the accuracy of the grating.

[0072] In step S3, the metal layer wire grid structure is gold, and a gold layer with a thickness of 150 to 250 nm is deposited using metal evaporation technology.

[0073] Specifically, a metal layer with a thickness of 150 to 250 nm is deposited on the etched SiO2 grating, and the metal material is gold (Au). Metal evaporation technology is used to deposit the metal layer, which evaporates gold at high temperature and deposits it on the sample surface to form a uniform and highly conductive metal film.

[0074] The following is an introduction in conjunction with specific embodiments:

[0075] First, a double-layer metal grating linear polarizer structure is designed. Its unit structure is in a regular geometric shape and is arranged periodically in the xy plane. Quartz is used as the substrate of the wire grid polarizer, SiO2 with good light transmittance in the near-infrared band is used as the dielectric grating material, and Au is used as the metal material. The specific structure is as follows: Figure 1 As shown. Among them, E, H, k represent the electric field vector, magnetic field vector and wave vector respectively; parameter P represents the period of the grating unit structure; parameter H represents the thickness of the metal grating layer Au structure; parameter h represents the thickness of the dielectric grating layer SiO2 structure; parameter W represents the width of the metal grating layer Au structure; parameter w represents the width of the dielectric grating layer SiO2 structure. f represents the duty cycle of the dielectric grating (f = w / P).

[0076] The double-layer grating polarizer structure is simulated using FDTD Solutions simulation software. In the simulation stage, the light source is set to a plane wave, with the direction vertically incident along the negative direction of the z-axis, and the band is selected as the design band of near-infrared 1 to 2 μm. The specific parameters of the designed structure are shown in Table 1.

[0077] Table 1 Geometric parameter settings of double-layer grating

[0078]

[0079] Under the same simulation conditions, single-layer metal gratings with grating widths of 80nm and 120nm were simulated. The metal material was Au, and compared with the double-layer grating structure in the present invention. The transmittance and extinction ratio (ER) curves are shown in Figure 2. Figure 2 The ER calculation formula is:

[0080]

[0081] Wherein, Tx and Ty represent the transmittance obtained under the incident x-polarized light and y-polarized light, respectively. In the figure, the black line represents the double-layer grating structure of the present invention, the blue line represents the single-layer metal grating structure with a grating width of 80nm, and the red line represents the single-layer metal grating structure with a grating width of 120nm. Next, according to the specific parameters of the structure of the present invention, the invention device is prepared. The specific preparation flow chart is as follows: Figure 3 The preparation method is as follows:

[0082] The quartz substrate was ultrasonically cleaned with acetone, isopropanol, and deionized water for 10 min each;

[0083] On the cleaned quartz substrate surface, 250nm thick non-doped SiO2 was deposited by PECVD;

[0084] Spin-coat ZEP520a positive photoresist on the SiO2 surface with a thickness of about 270nm, and pre-bake the photoresist at 180℃ for 2min.

[0085] Due to the non-conductivity of the sample, it is necessary to continue to use the spin coating method to spin-coat the Discharge+ conductive glue on the surface layer of the photoresist for subsequent electron beam exposure;

[0086] The sample after the glue is evenly coated is subjected to electron beam exposure, development, and fixing operations. The developer is amyl acetate, and the development time is about 70 seconds. The fixer is isopropyl alcohol, and the fixing time is about 30 seconds. Before the development and fixing operation, it is necessary to first remove the residual Discharge+ conductive glue on the sample surface, slowly spray the sample surface with deionized water for about 40-60 seconds, and blow dry with nitrogen;

[0087] After fixing, the sample was etched using ICP-RIE with an etching depth of 235 nm. After etching, the sample was stripped;

[0088] On the surface of the sample after degumming, a 195 nm thick Au layer was deposited using a metal evaporation method to complete the sample preparation.

[0089] The prepared samples were tested for performance. The specific test optical path diagram is as follows: Figure 4 As shown. The performance of the sample is characterized by using a Fourier transform infrared spectrometer (FTIR), and a polarizer (LP), an aperture (Aperture), a sample, an objective lens (Objective) and a detector (Photodetector) are placed therein. The transmittance through the sample device is detected by rotating the LP from 0° to 90°, and the extinction performance of the sample is verified using the extinction ratio formula.

[0090] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A high extinction ratio double-layer grating structure polarization device, comprising a quartz substrate, a SiO2 dielectric grating layer and a metal layer wire grid structure, characterized in that: The SiO2 dielectric grating layer is arranged on a quartz substrate; The metal layer wire grid structure is arranged on the SiO2 dielectric grating layer, and the metal layer wire grid structure and the SiO2 dielectric grating layer together form a double-layer grating structure; By adjusting the unit structure, thickness and grating width of the double-layer grating structure, the high extinction ratio double-layer grating structure polarization device has an extinction ratio of more than 75dB in the near-infrared band of 1 to 2μm.

2. The high extinction ratio double-layer grating structure polarization device according to claim 1, characterized in that: The thickness of the SiO2 dielectric grating layer is 200-300 nm, and the thickness of the metal gold grating layer is 150-250 nm.

3. The high extinction ratio double-layer grating structure polarization device according to claim 1, characterized in that: The period P of the unit structure of the double-layer grating is 150-250nm, the width W of the metal gold grating layer is 100-150nm, the width w of the SiO2 medium grating layer is 70-90nm, and the duty cycle f is 0.3-0.

5.

4. A method for preparing a high extinction ratio double-layer grating structure polarization device, characterized in that: The high extinction ratio double-layer grating structure polarization device according to any one of claims 1 to 3 comprises the following steps: S1. Cleaning the quartz substrate; S2, depositing a SiO2 layer on a quartz substrate; S3. Spin-coat photoresist on the SiO2 layer, perform exposure and etching, and form a metal layer wire grid structure by metal evaporation technology.

5. The method for preparing a high extinction ratio double-layer grating structure polarization device according to claim 4, characterized in that: In the step S1, the quartz substrate cleaning includes ultrasonic cleaning using acetone, isopropyl alcohol and deionized water for 5 to 15 minutes respectively.

6. The method for preparing a high extinction ratio double-layer grating structure polarization device according to claim 4, characterized in that: In the step S2, a non-doped SiO2 layer with a thickness of 200 to 300 nm is deposited on the substrate using plasma enhanced chemical vapor deposition.

7. The method for preparing a high extinction ratio double-layer grating structure polarization device according to claim 4, characterized in that: In the step S3, the thickness of the photoresist after spin coating is 250-300 nm, the pre-baking temperature is 150-200° C., and the time is 1-3 minutes.

8. The method for preparing a high extinction ratio double-layer grating structure polarization device according to claim 4, characterized in that: In the step S3, the SiO2 layer is etched by inductively coupled plasma reactive ion etching to a depth of 200 to 300 nm to form a grating structure.

9. The method for preparing a high extinction ratio double-layer grating structure polarization device according to claim 4, characterized in that: In the step S3, the metal layer wire grid structure is gold, and a gold layer with a thickness of 150 to 250 nm is deposited using metal evaporation technology.